Penatalaksanaan Terapi dengan dan tanpa Diet CFGF Terhadap Kemajuan Anak Autisme di Sekolah Al-Ikhlas Bukittinggi - Hendrawati Hendrawati; Ridhyalla Afnuhazi (Jurnal Pembangunan Nagari, 2017)
The purpose of this study was to determine the ratio of treatment management with and without free casein gluten free diet (CFGF diet) to the progress of autism children in Autism Al-Ikhlas Special School Bukittinggi. The research design used in this study is a type of Pre-Exsperimental Design research design using The Static Group Comparison design. The study took place in June 2014, with a sample of 30 people consisting of 15 children who underwent therapy with CFGF diet and 15 children who underwent Therapy without CFGF diet. Data analysis using Dependent T test and Independent T test. The results of this study can be concluded that the progress of children with autism who undergo behavioral therapy, speech therapy, occupational therapy with diet CFGF higher than those undergoing behavioral therapy, speech therapy, occupational therapy without diet CFGF. Suggestion management in children with autism requires early, integrated and intensive therapy by providing physical therapy (behavioral therapy, speech therapy, occupational therapy) and from within the body, such as the CFGF diet included in the biomedical therapy section.